Three-year patient-reported visual function outcomes in diabetic macular edema managed with ranibizumab: the RESTORE extension study. (2nd November 2015) - Mitchell, Paul; Massin, Pascale; Bressler, Susan; Coon, Cheryl D.; Petrillo, Jennifer; Ferreira, Alberto; Bressler, Neil M.
Abstract: Objective: To determine the impact of ranibizumab 0.5 mg on patient-reported visual function over 36 months in individuals with visual impairment from diabetic macular edema. Methods: RESTORE comprises a phase 3, randomized, multicenter, 12 month core study and a 24 month open-label extension study. Eyes assigned to ranibizumab in the core study received ranibizumab for 36 months; eyes assigned to laser monotherapy in the core study received ranibizumab during the extension. The primary outcome was least-squares mean change in National Eye Institute 25-item Visual Functioning Questionnaire (NEI VFQ-25) overall composite and subscale scores. Results: Of 303 core study participants, 240 (79%) entered the extension, comprising 83 (35%) participants initially assigned to ranibizumab, 83 (35%) assigned to ranibizumab plus laser combination therapy, and 74 (31%) assigned to laser monotherapy. Least-squares mean (standard error) change in NEI VFQ-25 composite score from baseline to month 12 (+5.9 [1.5]; +5.0 [1.5], for the ranibizumab and combination therapy groups, respectively) decreased by month 36 (+4.1 [1.7]; +4.0 [1.7], respectively, from baseline to month 36) following reduced injection frequency relative to the core study. At 36 months, the least-squares mean (standard error) change in the laser monotherapy group was similar to that in the ranibizumab groups (+4.1 [1.8]). Most subscale scores showed outcomes similar to that for the composite score. The greatest NEI VFQ-25 gains were consistently observed in participants for whom the study eye was the better-seeing eye. Limitations: Patients entering the extension were not randomized, and 21% of the core study participants did not enter the extension, which may have affected the results. Conclusions: Gains in patient-reported visual function at month 12 among eyes receiving ranibizumab in the core study decreased slightly by 36 months. Eyes originally receiving laser monotherapy for 12 months then ranibizumab for 24 months achieved similar gains by 36 months to eyes receiving ranibizumab for 36 months. Trial Registration: ClinicalTrials.gov: NCT00687804 and NCT00906464.